The teaching aids and technologies in today's education - Lazo Calderón, Tania de la Caridad (Revista Minerva, 2021)
The teaching aids are all those resources that the teacher uses in his class, with the aim of facilitating the teaching-learning process. The scientific-technical revolution has generated an accelerated production of knowledge, has precipitated the development of information and communication technology (ICT), as well as a marked dematerialization of production and services. ICTs are tools that enable the access, management, processing and dissemination of information in a society. The computerization process is part of the development of current Cuban society and is used with great success in the teaching-learning process.Today it is considered a means of teaching that the teacher uses so that his class can be understood by his students, within any educational context and information is easily accessed, develops abilities, skills, as well as attitudes and values.
Keywords: teaching-learning process; teaching aids; communication; development